The German market for system reserve capacity and balancing energy - Sebastian Just (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2015)
This paper provides the technical background, describes the market design and its development as well as summarizes the market results of the German system reserve capacity market and the balancing energy mechanism, which are the key tools for required balancing the of the electricity system.
Keywords: 330; system reserve capacity; balancing energy mechanism; German electricity market; market design